2021
DOI: 10.3390/ani11123451
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Probiotic Pediococcus acidilactici MA18/5M Improves the Growth, Feed Performance and Antioxidant Status of Penaeid Shrimp Litopenaeus stylirostris: A Growth-Ration-Size Approach

Abstract: Probiotics are increasingly documented to confer health and performance benefits across farmed animals. The aim of this study was to assess the effect of a constant daily intake of the single-strain probiotic Pedicococcus acidilactici MA18/5M (4 × 108 CFU.day−1.kg−1 shrimp) fed over fixed, restricted ration sizes (1% to 6% biomass.day−1) on the nutritional performance and metabolism of adult penaeid shrimp Litopenaeus stylirostris (initial body-weight, BWi = 10.9 ± 1.8 g). The probiotic significantly increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 87 publications
(140 reference statements)
0
4
0
Order By: Relevance
“…Potential alternatives to prevent disease outbreaks include vaccines and probiotics (Gram-negative or Gram-positive bacteria, yeasts, bacteriophages or unicellular algae) 50,58,59,[104][105][106] . Currently, a lactic acid bacterium-based product (Bactocell, a feed formulation prepared from the Gram-positive species Pediococcus acidilactici) 107 is on the market, and work on the commercial production of a Gram-negative Alphaproteobacteria from the Roseobacter group, particularly the species Phaeobacter inhibens, is underway 50 . However, the exact mechanisms by which such aquaculture probiotics work are unknown, which has led to new initiatives that base the selection of strains on the mode of action.…”
Section: Aquaculturementioning
confidence: 99%
“…Potential alternatives to prevent disease outbreaks include vaccines and probiotics (Gram-negative or Gram-positive bacteria, yeasts, bacteriophages or unicellular algae) 50,58,59,[104][105][106] . Currently, a lactic acid bacterium-based product (Bactocell, a feed formulation prepared from the Gram-positive species Pediococcus acidilactici) 107 is on the market, and work on the commercial production of a Gram-negative Alphaproteobacteria from the Roseobacter group, particularly the species Phaeobacter inhibens, is underway 50 . However, the exact mechanisms by which such aquaculture probiotics work are unknown, which has led to new initiatives that base the selection of strains on the mode of action.…”
Section: Aquaculturementioning
confidence: 99%
“…The intestinal microbial composition can reflect diet composition and digestive and absorption capacity, and then affect the growth of shrimp and crab hosts [23,24]. The intestinal microbiota plays a role in promoting health and growth in fishes, and it has also been found that the bacterial community can improve the metabolic capacity of carbohydrates and amino acids to enhance growth and survival [25].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it was found that feeding with immunopotentiators could regulate the glucose homeostasis in crustaceans (Zhang et al, 2021). For instance the concentration of glucose and glycogen was increased after feeding with probiotic Pedicococcus acidilactici in Litopenaeus stylirostris (Castex et al, 2021). Moreover, dietary carbohydrates (CBH) could also lead to the high levels of glucose and glycogen in L. stylirostris (Rosas et al, 2000).…”
Section: Discussionmentioning
confidence: 99%